2015
DOI: 10.1111/neup.12194
|View full text |Cite
|
Sign up to set email alerts
|

Lack of IDH1 mutation in astroblastomas suggests putative origin from ependymoglial cells?

Abstract: Astroblastomas are extremely rare neuroepithelial tumors of uncertain histogenesis, affecting children and young adults, and constitute a new addition to the WHO 2000 classification of CNS tumors. We report the largest series of nine cases diagnosed in a single institute over the last 13 years and review published literature. Mean age at presentation was 12.8 years (range: 22 months to 27years). Seven out of nine cases were supratentorial (frontal/frontoparietal - three, parieto-occipital - three, parafalcine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
5
9
1
Order By: Relevance
“…Because whole genome sequencing or RNA sequencing failed to show MN1 rearrangement, genetic aberrations of ependymomas seem to be different from the data shown in the present study . Therefore, astroblastoma is considered to be distinct from ependymoma in both clinicopathologic and genetic aspects, but there may be some relationship in cellular differentiation and histogenesis .…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Because whole genome sequencing or RNA sequencing failed to show MN1 rearrangement, genetic aberrations of ependymomas seem to be different from the data shown in the present study . Therefore, astroblastoma is considered to be distinct from ependymoma in both clinicopathologic and genetic aspects, but there may be some relationship in cellular differentiation and histogenesis .…”
Section: Discussioncontrasting
confidence: 89%
“…The clinical features of the eight cases collected based on the current criteria of astroblastoma were similar to those of the cases reported by Bonnin and Rubinstein (5), Brat et al (7), and others (2,17,19,34). All patients, but one, were children or young adults.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…One next-generation sequencing study of three cases identified mutations in a few genes known to be altered in low-grade gliomas, including BCOR, BCORL1, ERBB3, MYB and ATM, but no recurrent mutations were seen (5). Importantly, this study did not identify mutations in genes that are commonly altered in infiltrating astrocytoma, such as IDH1, ATRX or TP53, thus differentiating astroblastoma genetically from diffuse gliomas and validating previous immunohistochemical findings (2). In another immunohistochemical study of 28 cases, Lehman et al identified BRAF p.V600E mutant protein in 38% of cases, raising the possibility of genetic overlap between astroblastoma and other circumscribed glial neoplasms driven by MAPK pathway alterations such as pleomorphic xanthoastrocytoma, ganglioglioma and pilocytic astrocytoma (19).…”
Section: Introductionsupporting
confidence: 80%